Deletion of Mea6 in Cerebellar Granule Cells Impairs Synaptic Development and Motor Performance - Wang, Xin-Tai; Zhou, Lin; Cai, Xin-Yu; Xu, Fang-Xiao; Xu, Zhi-Heng; Li, Xiang-Yao; Shen, Ying (Frontiers in Cell and Developmental Biology, 2021)
The cerebellum is conceptualized as a processor of complex movements. Many diseases with genetic mutations, including Fahr’s disease associated with the loss-of-function mutation of Mea6 gene, exhibit cerebellar malformations and motor disorders. We previously reported that the defects in cerebellar development and motor performance are severer in Nestin-Cre;Mea6F/F mice than in Purkinje cell-targeted pCP2-Cre;Mea6F/F mice, suggesting that Mea6 acts on other types of cerebellar cells. Here, we investigated the function of Mea6 in cerebellar granule cells and found that mutant mice with specific deletion of Mea6 in granule cells displayed abnormal posture, balance and motor learning, as shown by footprint, head inclination, balanced beam and rotarod tests. We further showed that Math1-Cre;Mea6F/F mice exhibited disrupted migration of granule cell progenitors and damaged parallel fiber-Purkinje cell synapses, which may be ascribed to impaired intracellular transport of vesicular glutamate transporter 1 and brain-derived neurotrophic factor. The present findings extend our previous work and may help to better understand the pathogenesis of Fahr’s disease.